Socio-economic conditions of women under Saansad Adarsh Gram Yojana: A case study of Jayapur village of Arajiline block, district Varanasi - Sharma, Abhilasha; Singh, Suman (National Geographical Journal of India, 2022)
Saansad Adarsh Gram Yojana (SAGY) is a rural development programme and it was launched on 11 October 2014 with a mandate to develop three Adarsh Grams by 2019 and to substantially improve the quality of life of all sections of the population through improved basic amenities, higher productivity, enhanced human development, better livelihood opportunities, access to rights and entitlements especially for women and weaker sections. According to the census of 2011, in the Jayapur village, almost 46% of total females were illiterate, only 15% were main-worker and 29% of the total household was in the BPLcategory. In the present paper an attempt has been made to analyze the socio-economic condition of women after the implementation of SAGY in Jayapur village of Arajiline block, Varanasi District, U.P. The study is carried out in the adopted village of Prime Minister. The study is mainly based on a primary survey of data but secondary source of data also used from the Block Development Ofce, Gram Panchayat and Anganwadi Centres. Primary data were collected from 80 female respondents in the age group of 18-49 by using purposive sampling through the interview schedule. Both qualitative and quantitative techniques have used in this study. For a graphical representation of the data pie charts, bar diagram, Tables and maps have prepared by using M.S. Excel and Arc GIS software. The results show that inaccessibility of water and sanitation facilities is still a major problem for the women of this village because they spend a lot of time in collecting water through hand-pumps and wells even for using the toilets they stored the water. Due to water scarcity, most of the women used to defecate in open. Although, Availability of electricity has made the life of women very easy especially in the completion of household chores such as serving food for families, teaching their children and in doing some productive works. Hence, there is an improvement in the socio-economic condition of women after the implementation of the SAGY but it is not at a satisfactory level. There is a need to investigate the proper implementation and ll the required gap.